DETERMINANTS OF UNDERPRICED INITIAL STOCK: A STUDY ON THE INDONESIA STOCK EXCHANGE - Ekadjaja, Margarita; Rorlen , Rorlen; Siswanto, Halim Putera (Graduate Program of Universitas Tarumanagara, 2023)
In the company, the issuer also wants profit, so expect a high initial price. However, on the part of the underwriters on the contrary, they expect a low initial price because they are bound by the full commitment stock guarantee system that applies in Indonesia. This difference in interests causes the issuer to compromise a bit by setting a lower initial share price so that investors are interested in buying the launched initial shares. As a result, when conducting an initial public offering, the company has difficulty in determining the price because there is no reference so that there is a potential for underpriced shares to occur. This study to analyze the factors that influence the level of undepriced, which is focused on age, return on total assets, financial leverage and firm size. First, the test will be carried out partially with a t-test to test the effect of each factor on the level of underpriced initial shares. Furthermore, the test will be carried out simultaneously with the F-test, namely to test the effect of the four factors together on the level of underpriced initial shares. The population in this study are companies that offer their initial shares on the Indonesia Stock Exchange and have underpricing stock values. The results show that company age has a positive effect on underpriced initial shares, while the return on total assets, financial leverage and firm size variables get the opposite result.